PENENTUAN PRIORITAS PASIEN BERDASARKAN RIWAYAT PENYAKIT DENGAN MENGGUNAKAN METODE AHP DI PUSKESMAS BANGGAI LAUT (Studi Kasus: Uptd Puskesmas Banggai) - Dita Andriani; Salihi, Irvan Abraham; Melangi, Sudirman (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2025)
Abstract Disease history-based patient prioritization is a vital step in health care, especially in situations of limited medical resources. The Analytical Hierarchy Process (AHP) method is used to calculate the level of importance of weighting all criteria and alternatives that produce appropriate and relevant reference values for patient prioritization. The criteria consideration covers blood pressure, heart rate, respiratory frequency, and temperature. Based on the calculation of weights from the AHP method, patients with the highest weights are recommended as prioritized patients. The results of this study indicate that medical history-based patient prioritization using the Analytical Hierarchy Process is implementable. The implementation result of the Analytical Hierarchy Process is proven following the test line conducted with Blackbox And Whitebox CC= 4. The disease history-based patient prioritization can help the Local Technical Implementation Unit of Banggai Health Center. Keywords: patient prioritization, disease history, AHP method